Promosi agen pelancongan melalui internet - Afifah, Binti Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2002)
The Internet travel agent (ITA) was compiled to be published and broadcasted in the Internet in order to attract more tourists to visit Sarawak. It is a portal that can help tourists to know more about beautiful and fascinating places here in `The land of hornbill'. This interactive travel portal promotion via Internet was developed in Windows 98 version by using the Hypertext Markup Language (HTML). As the programming in the interface, Flash 5 was used while the Active Server Page (ASP) was used as the programming language for the functions. Beside that, Microsoft Driven access also being used to developed the database for the purpose of storing certain data.